Adat Berguru Pranikah pada Suku Gayo di Desa Serule Kayu Kecamatan Bukit Perspektif Maṣlaḥah Mursalah - Saragih, Muhammad Faisal Afif; Khalid, Khalid (AL-SULTHANIYAH, 2026)
This study examines the edet beguru tradition among the Gayo ethnic community in Serule Village, Bener Meriah Regency. Edet beguru refers to the practice of giving advice, guidance, and moral instruction to the bride and groom as preparation for building a harmonious household. This research employs an empirical approach conducted in Serule Village, Bener Meriah. Data were collected through observation and interviews with traditional leaders, religious scholars, and local residents, and analyzed using the Ushul Fiqh framework with the maṣlaḥah mursalah method. The findings indicate that the traditional wedding ceremony of the Gayo community in Serule Village consists of twelve stages, including munginte, sesuk pantang, teniron, iserahan ku guru, sedelung, nik mas, sawah ukum, mah bai, dalem, membilang emas, beru, and mah beru. The edet beguru tradition is carried out in two forms: one day before the ijab kabul or on the wedding day before the marriage contract. This procession serves as moral and religious education, covering creed, ethics, customs, and the rights and obligations of the couple. Based on maṣlaḥah mursalah analysis, edet beguru is considered sunnah (recommended), originally mubah (permissible), as it contains significant social and spiritual benefits.